Nestor, Barbara (audio interview #4 of 10) - Nestor, Barbara (9/29/1884 - 11/1/1979); Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - As in previous interviews, Nestor was enthusiastic and energetic during this third interview. The audio quality is good, although the interview was interrupted on a few occasions because of background noise and skips in the recording, particularly during the second half of the interview. 11/15/1974